Host-country market environment, intra-firm technology transfer performance and corporate sustainability: A conceptual study - Syed Ali Fazal; Sazali Abdul Wahab; Abu Sofian Yaacob; Nur Fadiah Mohd Zawawi (Canadian Center of Science and Education, 2016)
Technological innovations have emerged as crucially significant factor for sustaining market competition and achieving sustainable competitive advantage in the 21st century. The Multinational Corporations (MNCs) as celebrities of innovation play significant role in diffusing technological knowledge throughout firms both nationally and internationally. Although numerous studies exist on technology transfer the majority of existing literature addresses the issues related to inter-firm transfer of technology only while the area related to intra-firm transfer of technology has been largely underexposed; study of which is believed to be ideal for fruitful exploration of profitability in technology transfer projects. By exploring the existing relevant literature, the current study would attempt to posit a new model in regards to the effect of host-country market factors on the performance of technology transferred by the MNCs and its subsequent impact on corporate sustainability. In the present study the relative influence of two market environment factors of the host-country, competitive intensity and market dynamism have been focused on and the study is thereby expected to contribute both theoretically in the body of knowledge and also in terms of practical implication for policy makers and MNCs and hence enriching the existing intra-firm literature simultaneously.